Chemical Characterization and Bioactive Properties of Different Extracts from Fibigia clypeata, an Unexplored Plant Food - Zengin, Gokhan (Foods, 2020)
Fibigia clypeata (L.) Medik. is a poorly studied plant species belonging to the Brassicaceae family, and usually used as cress in the salads. The current investigation aimed at assessing the antioxidant potential and inhibitory activity of ethyl acetate, methanol, and aqueous extracts of F. clypeata against key enzymes targeted in the management of type II diabetes (α-amylase and α-glucosidase), Alzheimer’s disease (acetylcholinesterase and butyrylcholinesterase), and skin hyperpigmentation (tyrosinase). Cytotoxicity of the extracts was also determined using normal VERO and cancer FaDu and SCC-25 cell lines. Besides, LC-MS was employed to investigate the detailed phytochemical profiles of the extracts. The methanol extract showed potent enzyme inhibitory activity (4.87 mg galantamine equivalent/g, 3.52 mg galantamine equivalent/g, 126.80 mg kojic acid equivalent/g, and 24.68 mg acarbose equivalent/g, for acetylcholinesterase, butyrylcholinesterase, tyrosinase, and α-glucosidase, respectively) and antioxidant potential (96.52, 109.10, 154.02, and 104.85 mg trolox equivalent/g, for DPPH, ABTS, CUPRAC, and FRAP assays, respectively). Interestingly, caffeic acid-O-hexoside derivative, caffeyl alcohol O-glucopyranoside, and ferulic acid derivative were identified in all extracts. F. clypeata extracts showed no cytotoxicity towards VERO cell line and a weak cytotoxic potential against FaDu and SCC-25 cell lines. Interesting scientific evidence gathered from the present study support further investigation on F. clypeata in the view of designing and developing a novel therapeutic agent for the management of Alzheimer’s disease, type II diabetes, skin hyperpigmentation problems, as well as cancer.